Production of lipase using palm oil mill effluent based medium by liquid state bioconversion - Salihu, Aliyu (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
Lipases are enzymes secreted by several microorganisms that can catalyze both hydrolytic and synthetic reactions. The challenges associated with the expansion of lipase technology on large scale include production cost, strain selection and modification, improvement of medium compositions and process parameters in enhancing the production. This work screened ten microorganisms for their potentials to produce lipase using palm oil mill effluent (POME) as an abundant and cheap renewable agro-industrial residue through fermentation techniques. The most promising strain was Candida cylindracea (ATCC 14830) based on qualitative and quantitative screening experiments. Sequential optimization strategy based on statistical experimental design including one-factor-at-a-time (OFAT) method was used to enhance the C. cylindracea lipase production in shake flask cultures. Response surface methodology (RSM) based on face-centered central composite design (FCCCD) developed a POME-based medium containing 0.45% (w/v) peptone, 0.65% (v/v) Tween-80 and 2.2% (v/v) inoculum which led to a maximum lipase production of 20.26 U/ml after 144 hrs of incubation. The analysis of variance indicated that the established model was significant (p <0.05). Using the optimized medium, process parameters (temperature, agitation, aeration) were also studied in 2-L bioreactor using a two-level full factorial design (FFD). It was found that bioreactor based production resulted in further increase in the overall lipase production. On statistical analysis of the results, the optimum temperature, aeration and agitation rates were found to be 30oC, 1.0 vvm and 400 rpm respectively, with a maximum lipase activity of 41.46 U/ml after 36 hrs of fermentation. Analysis of variance (ANOVA) showed a high coefficient of determination (R2) value of 0.999, indicating a satisfactory fit of the model with the experimental data. As part of the upscaling strategies, the established optimum process conditions were transferred to 30-L bioreactor and the lipase production slightly increased to 43.19 U/ml. Following the cross flow filtration and chromatographic techniques, the temperature and pH optima of the enzyme were found to be 35oC and 8 respectively with apparent molecular mass of 58 kDa by SDS-PAGE. Among the divalent cation salts tested, Ca2+ and Mn2+ activated the enzyme most, while Cu2+ and Fe2+ inhibited it. Non-ionic detergents and water miscible organic solvents appeared to have stimulatory and inhibitory effects on lipase activity respectively. The esterification potential of the produced enzyme was verified using FCCCD, and it was found to be 63.36% based on butyl butyrate formation. Thus, the lipase production obtained in this study shows some potential in meeting the target of reducing the production costs with increased productivity possessing some desirable characteristics. Based on this, the study showed that bioconversion of POME for lipase production would hold a prominent position in future biotechnologies mainly because of its eco friendliness and flexibility for the economic development of the country.